IL36G is associated with cutaneous antiviral competence in psoriasis - Lu, You-Wang; Chen, Yong-Jun; Shi, Nian; Yang, Lu-Hui; Wang, Hong-Mei; Dong, Rong-Jing; Kuang, Yi-Qun; Li, Yu-Ye (Frontiers in Immunology, 2022)
Background:Psoriasis is a common inflammatory skin disease that has a great impact on physical and mental health. However, the cause and underlying molecular mechanisms of psoriasis is still largely unknown.Methods: The expression profiles were integrated by sva package, and differentially expressed genes (DEGs) between psoriasis and healthy skin were screened by limma package. Furthermore, the GO and KEGG pathway enrichment of DEGs were performed using Clusterprofiler package. Then protein–protein interaction (PPI) networks of the DEGs was constructed to identify hub genes. scGESA analysis was performed on single-cell RNA sequencing dataset by irGSEA. In order to find the cytokines correlated with the hub genes expression, single cell Weighted gene co-expression network analysis (scWGCNA) were utilized to build a gene co-expression network. Furthermore, the feature genes of psoriasis in suprabasal keratinocytes were intersected with hub genes. Then, we analyzed expression the intersection genes and cytokines in the integrated dataset. After that, we used other datasets to reveal the changes in intersection genes expression level during the biologist therapy. The relationship between intersection genes and PASI was also being explored.Results: We identified 148 DEGs between psoriasis and healthy samples. GO and KEGG pathway enrichment analysis suggested that DEGs are mainly involved in the defense response to other organism. The PPI network showed that 11 antiviral proteins (AVPs) were hub genes. scGSEA analysis in single cell transcriptome dataset showed that those hub genes are highly expressed in keratinocytes, especially in suprabasal keratinocytes. ISG15, MX1, IFI44L and IFI27 were the characteristic genes of psoriasis in suprabasal keratinocytes. scWGCNA showed that three cytokines IL36G, MIF and IL17RA were co-expressed in turquoise module. Only IL36G were positivity correlated with AVPs in the integrated dataset. IL36G and AVPs were found co-expressed in substantial suprabasal keratinocytes. Furthermore, we found that IL36G and the 4 AVPs expression level showed positive correlation with PASI in patients with psoriasis and their levels were decreased significantly during the treatment of biologicals therapy but not using Methotrexate.Conclusion: IL36G and antiviral proteins may be closely related with pathogenesis of psoriasis, and they may represent new candidate molecular markers of the occurrence and severity of psoriasis.